Correlation between dislocation organization and slip bands: TEM and AFM investigations in hydrogen-containing nickel and nickel–chromium. (1st June 2015) - Girardin, G.; Huvier, C.; Delafosse, D.; Feaugas, X.
Abstract: Various forms of the plastic deformation in single crystals are studied in pure and hydrogen-containing nickel and nickel alloys oriented for single slip [1 3 5] and strained in the stage III regime (shear strain, γ  = 0.8). The heterogeneity of deformation is investigated at two distinct scales: slip bands and dislocation structures, using atomic force microscopy (AFM) and transmission electronic microscopy (TEM). Size and distribution of slip band thicknesses and geometrically necessary boundary (GNB) spacing are comparable. GNB structures both screen the long-range stress fields and decrease the mean free path of mobile dislocations, whereas equiaxed cells only impede dislocation motion through their role as obstacles. Consequently, GNB formation localizes deformation in specific slip bands. Additionally, the observed similarity between GNB spacing and equiaxed cell size suggests a correlation between these microstructural features. The impact of solid solution atoms on the inter-wall spacing is established for chromium and hydrogen. Both decrease the GNB spacing because of a decrease of the cross-slip probability and stacking fault energy, combined to a shielding effect for the later. The effect of GNB spacing on strain hardening is discussed in terms of the length scale associated with GNBs and the effect of solute content.